2018
DOI: 10.1161/jaha.117.008441
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Family Member Insulin‐Like Peptide 6 Ameliorates Cardiac Fibrosis and Prevents Cardiac Remodeling in Murine Heart Failure Models

Abstract: BackgroundThe insulin/insulin‐like growth factor/relaxin family represents a group of structurally related but functionally diverse proteins. The family member relaxin‐2 has been evaluated in clinical trials for its efficacy in the treatment of acute heart failure. In this study, we assessed the role of insulin‐like peptide 6 (INSL6), another member of this protein family, in murine heart failure models using genetic loss‐of‐function and protein delivery methods.Methods and ResultsInsl6‐deficient and wild‐type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…(Chow et al, 2012;Chow et al, 2014;Mookerjee et al, 2009;Sarwar et al, 2015;Wang et al, 2016;Wetzl et al, 2017;Wetzl et al, 2016 (Hossain et al, 2016;Praveen et al, 2017) Relaxin-3 RXFP1, RXFP3? Cardiac fibrosis unknown NLRP3-inflammasome Collagen MMPs (Hossain et al, 2011;Zhang et al, 2018;Zhang et al, 2017) InsL6 unknown Cardiac fibrosis unknown TGFβ collagen (Maruyama et al, 2018)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Chow et al, 2012;Chow et al, 2014;Mookerjee et al, 2009;Sarwar et al, 2015;Wang et al, 2016;Wetzl et al, 2017;Wetzl et al, 2016 (Hossain et al, 2016;Praveen et al, 2017) Relaxin-3 RXFP1, RXFP3? Cardiac fibrosis unknown NLRP3-inflammasome Collagen MMPs (Hossain et al, 2011;Zhang et al, 2018;Zhang et al, 2017) InsL6 unknown Cardiac fibrosis unknown TGFβ collagen (Maruyama et al, 2018)…”
Section: Resultsmentioning
confidence: 99%
“…Hence, relaxin-3 (acting via RXFP1, and possibly via RXFP3) might be therapeutically relevant for the treatment of diabetic cardiomyopathy. A recent study showed that mice lacking insulin-like peptide 6 (Insl6), a member of the relaxin family, exhibit cardiac dysfunction and enhanced cardiac fibrosis, suggesting the role of Insl6 in suppressing cardiac fibrosis and its potential to be used for the treatment of heart failure (Maruyama et al, 2018). Further studies are needed to determine if relaxin-3 or Insl6 can be used to treat established models of tissue fibrosis.…”
Section: Emerging Potential Relaxin-based Antifibrotic Therapiesmentioning
confidence: 99%
“…Our previous study reported that insulin-like peptide 6 (INSL6) inhibits cardiac fibrosis in cardiac stress models 1 . In the process, we found that tissue nonspecific alkaline phosphatase (TNAP) was upregulated both in fibrotic heart and in the kidney, and was depressed by INSL6, indicating a role on fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…We rank selected single nucleotide polymorphisms (SNPs) (370 SNPs for African American and 217 for Caucasian) based on their p-value in the logistic regression and conduct the gene set enrichment analysis for genes in which top 10 SNPs reside. For African American, genes for top 10 important SNPs are COL24A1, INSL6, MTTP, ATF7IP, CUBN, SLC39A12, ZNF208, LPIN3, UTRN; COL24A1, INSL6, MTTP, ATF7IP, CUBN, SLC39A12, and ZNF208 and are showed to have close relationship to cardiac functions [21][22][23][24][25][26]. For Caucasian cohort, genes for top 10 important SNPs are DNHD1, ASPM, TTC21B, GMPS-KCNAB1, HEATR1, OR10J1, and LGALS8; except for DNHD1, all other genes are related to cardiovascular function [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%